2001
DOI: 10.1089/089277901300189501
|View full text |Cite
|
Sign up to set email alerts
|

Results and Side Effects of High-Intensity Focused Ultrasound in Localized Prostate Cancer

Abstract: At the time of diagnosis, prostate cancer is organ confined in 70% of the cases. A quarter of these patients undergo local therapy (surgery/radiation); 75% risk disease progression by "watchful waiting" or systemic side effects through hormonal ablation. Local high-intensity focused ultrasound (HIFU), as minimal invasive tissue coagulation (85 degrees C), ablates prostatic tissue with high precision. Since April 1996, 184 patients have undergone 232 sessions of transrectal HIFU therapy (average 90 min) under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 8 publications
(4 reference statements)
1
75
0
5
Order By: Relevance
“…Since then, many studies have confirmed the efficacy and safety of HIFU in the treatment of early localized PCa. 17,18 However, clinical results have shown a substantially increased ratio of biochemical recurrence and positive biopsy among the patients with high-risk or locally advanced PCa who underwent HIFU therapy. 19,20 This may have resulted from the following factors: (i) the ultrasound positioning system could not accurately demarcate the invasive margin of advanced PCa, which led to the insufficiency of treatment; and (ii) patients with high-risk or locally advanced PCa had a high risk of pelvic lymph node involvement due to the blind zone beyond target areas of HIFU treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, many studies have confirmed the efficacy and safety of HIFU in the treatment of early localized PCa. 17,18 However, clinical results have shown a substantially increased ratio of biochemical recurrence and positive biopsy among the patients with high-risk or locally advanced PCa who underwent HIFU therapy. 19,20 This may have resulted from the following factors: (i) the ultrasound positioning system could not accurately demarcate the invasive margin of advanced PCa, which led to the insufficiency of treatment; and (ii) patients with high-risk or locally advanced PCa had a high risk of pelvic lymph node involvement due to the blind zone beyond target areas of HIFU treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our centre does not perform nerve-sparing HIFU because of the oncological risk and the likelihood of repeat treatment. 3,26,27 Repeat HIFU carries a significantly higher risk of impotency and incontinence. 28 Specific criteria have been established for repeat treatment because of the lesions occurring after a first procedure 29,30 and the HIFU treatment of localized prostate cancer T Ripert et al problems in detecting prostate boundaries for a repeat procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These DEGs retrieved are important for investigating the mechanism of disease development from Prostate cancer. It is well known that Prostate Cancer treatment has severe side effects, which necessitate the need to find better chemotherapeutic agents (Chaussy et al, 2001). …”
Section: Identification Of Degsmentioning
confidence: 99%